1964
DOI: 10.1021/bi00893a021
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Exclusion and Restricted Diffusion Processes in Molecular-Sieve Chromatography*

Abstract: From experimental measurements of equilibrium solute partitioning and of corresponding column elution volumes with Sephadex gels, there appear to be two primary molecular sieving effects responsible for the commonly observed variation of elution position with molecular size. The first is a simple exclusion effect presumably due to dimensional heterogeneity of the gel interstices. This effect is of primary importance in the more tightly cross-linked G-75 and G-100 gels. The second effect is a steric and frictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
195
1
1

Year Published

1970
1970
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 789 publications
(205 citation statements)
references
References 25 publications
8
195
1
1
Order By: Relevance
“…The Stokes' radius of protein S4 was determined from a logarithmic plot of Ro versus elution volume [erf-' (l-KD)], after calibration of the column with standard proteins of known Stokes' radius, by determining the distribution coefficient, KD, according to Ackers [25].…”
Section: Gel Filtrationmentioning
confidence: 99%
“…The Stokes' radius of protein S4 was determined from a logarithmic plot of Ro versus elution volume [erf-' (l-KD)], after calibration of the column with standard proteins of known Stokes' radius, by determining the distribution coefficient, KD, according to Ackers [25].…”
Section: Gel Filtrationmentioning
confidence: 99%
“…r: effective gel-pore radius (Ackers, 1964). cate analyses of y-FA from both em bryo and QUA tumour showed that the antigen from either source had about the same Stokes radius (Table II).…”
Section: Methodsmentioning
confidence: 99%
“…The peak of y-FA elution was determined by radial immunodiffusion assay of lOul aliquots from each fraction. The Stokes radius of y-FA derived from tumour and embryo was calculated according to Ackers (1964) using data obtained from duplicate analyses.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations